Low ankle-brachial index and cognitive function after stroke—the PROSpective with Incident Stroke Berlin (PROSCIS-B) - Stillfried, Maria R. V.; Sperber, Pia S.; Broersen, Leonie H. A.; Huo, Shufan; Piper, Sophie K.; Heuschmann, Peter U.; Endres, Matthias; Siegerink, Bob; Liman, Thomas G. (Frontiers in Neurology, 2022)
Introduction: Low ankle-brachial index (ABI) ≤0.9 is a marker for generalized atherosclerosis and a risk factor for cognitive decline in the general population. Objective: To evaluate the impact of ABI≤0.9 on cognitive function up to three years after first-ever ischemic stroke. Methods: Data was used from the `PROSpective Cohort with Incident Stroke-Berlin’ (PROSCIS-B; NCT01363856). ABI was measured at baseline and categorized into normal (1.4–0.9) versus low (≤0.9). Cognitive function was assessed with the Montreal Cognitive Assessment (MoCA) and the Mini-Mental-State-Examination (MMSE) at baseline and with the Telephone Interview for Cognitive Status-modified (TICS-m) at 1 to 3 years of follow-up. We performed confounder adjusted generalized linear models (GLM) to calculate relative risks (RR) for cognitive impairment at baseline (MMSE≤26; MoCA≤25) and linear mixed models (LMM) to estimate the impact of low ABI on TICS-m over time. Results: We included 325 patients (mean age: 66 [SD=13]; 38% female, median NIHSS=2 [IQR=1–4], ABI≤0.9: 59 [18%]). Patients with low ABI were at increased risk of cognitive impairment at baseline (adjusted RR for MoCA ≤25=1.98;95%-CI:1.24 to 3.16). TICS-m scores were consistently lower over time in patients with low ABI (adjusted ß=-1.96;95%-CI:-3.55 to -0.37). Independent of ABI, cognitive function did not decline over time (adjusted ß:0.29;95%-CI:-0.06 to 0.64). Conclusion: In patients with mild to moderate first-ever ischemic stroke, low ABI is associated with reduced cognitive function over a three-year follow-up.